EFFECT OF NEEMTA 2100 TOXICITY ON ACETYLCHOLINESTERASE AND SERUM GLUTAMATE OXALOACETATE TRANSAMINASE ENzynms IN SERUM OF FISH, OREOCHROMIS MOSSAMBICUS - Parveen, Mahira; Sharma, Ritu; Kumar, Santosh (Journal of Indian Fisheries Association, 2015)
Acetylcholinesterase and Serum glutamate oxaloacetate transaminaseenzymes have been used as marker monitoring the effect of neem seed basedpesticide Neemta 2100 on the fish, Oreochromis mossambicus. Fishes exposedto sublethal concentrations of neemta 2100 for acute periods of 24 and 48hours were sacrificed to determine enzyme activities in serum affected dueto toxicity. Laboratory studies of in vivo exposure of this pesticide showedsynergistic inhibitory effect during acute period of toxicity.Acetylcholinesterase was noticed as 6.25 J.Uil substrate hydrolyzed I mg proteinI hour and Serum glutamate oxaloacetate transaminase was noticed as 36.71J.Uil substrate hydrolyzed I mg protein I hour in control fish serum. Significantdecrease in GOT level in Neemta 2100 treated fishes after short term exposureindicated its severe toxicity to fish.Key words: Serum, Neemta 2100, Enzymes, Fish